2001
DOI: 10.1002/ajim.1073
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and lung function in workers in heavy and highway construction: A cross‐sectional study*

Abstract: TWs, laborers, and OEs in HH construction are at increased risk for asthma. TWs also appear to be at increased risk for chronic bronchitis. Our data suggest that symptomatic workers are self-selecting out of their trade. Asthma was associated with lower lung function in those affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…Prevalence of physician-diagnosed asthma ranged from none among ironworkers to 8.2% among laborers and 9.7% among operating engineers. These findings are consistent with our earlier finding of physician-diagnosed asthma in 8.2% of laborers (including tunnel workers) and 10.8% of operating engineers [Oliver et al, 2001]. The reporting of SCA by 45% of those with diagnosis of asthma but without ''current asthma'' suggests aggravation of pre-existing asthma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Prevalence of physician-diagnosed asthma ranged from none among ironworkers to 8.2% among laborers and 9.7% among operating engineers. These findings are consistent with our earlier finding of physician-diagnosed asthma in 8.2% of laborers (including tunnel workers) and 10.8% of operating engineers [Oliver et al, 2001]. The reporting of SCA by 45% of those with diagnosis of asthma but without ''current asthma'' suggests aggravation of pre-existing asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence is high compared to our earlier study (4.6%) [Oliver et al, 2001] and similar to that of Tjoe-Nij et al [2003], who found that 10% of workers reported chronic cough with sputum. Twenty-nine percent of participants reported SOB.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rubber and plastic workers are usually exposed to a variety of chemicals, including low molecular weight agents, such as azidocarbonamide and isocyanate compounds known to be risk factors for asthma [Venables and Chan-Yeung, 1997;Singh and Davis, 2002]. Significantly increased risk for asthma in construction work was observed among women and men in population-based and industry-based studies [Ng et al, 1994;Karjalainen et al, 2001;Oliver et al 2001]. Possible hazards in construction industry that might be associated with the development of asthma include cement, concrete dusts, welding, and asphalt fumes [Oliver et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…102 Epidemiological studies have also reported an increased risk of chronic bronchitis in populations of workers exposed to a wide range of other fumes, dusts, gases, and vapors. Examples include food processors, 103 chemical workers, 103 welders, 104 painters, 105 tunnelers, 106 steel mill workers, 107 and poultry handlers. 108 The cough of occupational chronic bronchitis should improve with a reduction in workplace irritant exposures, 109 in the same way that the chronic cough related to smoking improves with quitting.…”
Section: Chronic Bronchitismentioning
confidence: 99%